Screening anti-inflammatory and neuroprotective effects of nanozyme with human cortical organoid-on-a-chip - Guojian Wu; Hong Wang; Lukui Chen (APL Materials)
Neuroinflammation plays a vital role in neural development as well as the pathogenesis and progression of neurodegenerative diseases. It is recognized as a promising therapeutic target for neurological disorders. Although multiple anti-inflammatory drugs have been examined for their therapeutic potential in neurodegenerative diseases, the development of new model systems to evaluate the safety and efficiency of anti-inflammatory agents is still greatly needed. Here, we presented a human cortical organoid-on-a-chip for modeling neuroinflammation and exploring the neuroprotective activity of cerium oxide (CeO2) nanozyme, a novel antioxidant, on neuroinflammation-induced neurotoxicity. hiPSC-derived cortical organoids, resembling the key characteristics of early human brain development, were generated on micropillar arrays. We showed that lipopolysaccharide (LPS) treatment induced inflammatory responses and neurological impairments in cortical organoids. Notably, the adverse responses caused by LPS administration could be effectively attenuated by treatment with nanozyme at a proper concentration, indicating that the CeO2 nanozyme exerts anti-neuroinflammatory and neuroprotective effects and could serve as a potential candidate to alleviate neuroinflammation-associated diseases. Together, the human cortical organoid-on-a-chip model presents a biomimetic system to investigate the complicated impacts of neuroinflammation on neural development and exhibits high potential in neurological study and drug evaluation.